Fossil eggshell diversity of the Mussentuchit Member, Cedar Mountain Formation, Utah - Joshua Hedge; Ryan T. Tucker; Peter J. Makovicky; Lindsay E. Zanno (PLoS ONE, 2025)
The first fossil eggshell from the Cenomanian-age Mussentuchit Member of the Cedar Mountain Formation was described over fifty years ago. In the half-century since, oodiversity of this rock unit has been limited to a single, taxonomically unstable ootaxon, currently formulated as Macroelongatoolithus carlylei. Recently, there has been a renewed effort to recover and describe the macrofauna of the Mussentuchit; however, these advances are limited to the body fossil record. Here, we examine the range of eggshells present in the Mussentuchit Member and assess the preserved biodiversity they represent. Gross morphological and microstructural inspection reveals a greater diversity of eggshells than previously described. We identify six ootaxa: three Elongatoolithidae oogenera (Macroelongatoolithus, Undulatoolithus, Continuoolithus), eggs laid by oviraptorosaur dinosaurs; two oospecies of Spheroolithus laid by ornithopod dinosaurs; and Mycomorphoolithus kohringi, laid by a crocodylomorph. The diversity of Elongatoolithidae in the Mussentuchit requires a co-occurrence of at least three putative oviraptorosaurs, the oldest such phenomenon in North America. The occurrence of the crocodylomorph oogenus Mycomorphoolithus is the first recognized occurrence outside of Europe, and the youngest yet documented. This new ooassemblage is more representative of the known paleobiodiversity of Cenomanian-age strata of Western North America and complements the body fossil record in improving our understanding of this crucial—yet poorly documented—timeslice within the broader evolution of the Cretaceous Western Interior Basin.